Improving the Skills of High School Teachers in Pinrang Regency in Utilizing Quizizz Application as Gamification-Based Interactive Learning Media - Muhammad Ansarullah S. Tabbu; Asri Ismail; Akhmad Affandi; Asham Bin Jamaluddin; Nurdin; Indrayani (Vokatek : Jurnal Pengabdian Masyarakat, 2024)
The role of teachers in creating interactive and interesting learning is very important in today's digital era. This Community Service Program (PKM) aims to improve the skills of high school teachers in Pinrang Regency in using the Quizizz application as a gamification-based interactive learning media. Through training and mentoring, this program seeks to overcome the obstacles of limited teacher skills in utilizing interactive learning technology. Observations and interviews show that most teachers are not familiar with the Quizizz application, which has an impact on low student motivation and learning outcomes. This PKM is implemented through training and mentoring methods at the Pinrang Regency Education Office. The training results show a significant increase in teachers' understanding and skills using the application, which directly improves teacher creativity and student learning motivation. This program is expected to improve the quality of learning and have a positive impact on student learning outcomes in Pinrang District.